FACTORS THAT INFLUENCE THE INTENTION OF STUDENTS TO PURSUE QUALIFICATION AS PROFESSIONAL ACCOUNTANTS (An Empirical Study of Undergraduate Accounting Students of Brawijaya University, Malang State University, and Maulana Malik Ibrahim Islamic State University, 2015) - NURUL QOMARIYAH (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
The aim of this study is to examine the factors that influence the intention ofstudents to pursue qualification as professional accountants. These factors consist of salary, opportunities for advancement, prestige or social status, job security and stability, and grit personality. The respondents in this study areundergraduate accounting students of Brawijaya University, Malang StateUniversity, and Maulana Malik Ibrahim Islamic State University in 2015. Datafrom 245 students were collected by the survey method by distributing an online questionnaire. Data analysis was performed using the SmartPLS 3.2.7application. The results proved that salary, job security and stability, and gritpersonality affected the intention of students to pursue qualification asprofessional accountants. Meanwhile, opportunities for advancement and prestige or social status did not affect the intention of students to pursue qualification as professional accountants. The implication of this study is that the Accounting Department of various universities can find out what factors can encourage the intention of accounting students to pursue qualification professional, in order to increase the number of professional accountants in Indonesia.Keywords: salary, opportunities for advancement, prestige or social status, job security and stability, grit personality, professional accountantqualification, professional accountants